Uma análise das leis sobre o consumo de substâncias psicoativas na Colômbia (1920-2012) - BENJUMEA, Diego Fernando Carvajal (2018)
This research analyzes how, based on the problematic of the consumption of psychoactive substances in Colombia, the State produces a context of population control (bodies and borders), through enactment of laws, legislative documents and international conventions, between the years 1920 – 2012. Prioritizing the analysis of Colombian legislation, to understand how in contemporary societies is exerted a power that influences the emergence of speeches such as “legal/illegal”, “normal/unusual” and classifies different types of people as “trader/trafficker”, “consumer/addict” – adjectives that indicate, include and exclude subjects from different spheres. This analysis allows observing the transformation in front of the designations that are made in reference to the person, the institutions, the specialists and the punishments on the theme; transmitted through laws, according to social dynamics and dominant thoughts of each historical moment. Thus, it is identified as the drug user has been classified as "criminal" and/or "sick", through legal documents corresponding to the years 1920 – 2012.